1991
DOI: 10.1111/j.1751-1097.1991.tb02062.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOCHEMISTRY ON SURFACES: TRIPLET‐TRIPLET ENERGY TRANSFER ON MICROCRYSTALLINE CELLULOSE STUDIED BY DIFFUSE REFLECTANCE TRANSIENT ABSORPTION and EMISSION SPECTROSCOPY*

Abstract: Triplet‐triplet energy transfer has been studied between benzophenone and an oxazine dye (2,7‐bis(diethyl‐amino)‐phenazoxonium chloride) co‐adsorbed on the surface of microcrystalline cellulose. Ground state absorption and fluorescence measurements provide evidence for dimer formation of the oxazine dye when adsorbed on cellulose in contrast to the behaviour in ethanol solution where no dimerization is observed. The equilibrium constant for dimerization, which is found to be (1.0 × 0.1) × 106 mol−1 g (2560 × 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Adsorbed species are immobilized in the rigid cellulose matrix by hydrogen bonding between the hydroxyl groups of the polymer chain and the guest molecule, reducing the molecular motion and increasing the adsorbate emission lifetime and quantum yield as reported in many cases. It was also reported that dyes adsorbed on cellulose are protected from quenching by molecular oxygen, as the mobility of this species is highly reduced in this medium, provided cellulose is well dried (20). In this way, interference from oxygen is easily avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbed species are immobilized in the rigid cellulose matrix by hydrogen bonding between the hydroxyl groups of the polymer chain and the guest molecule, reducing the molecular motion and increasing the adsorbate emission lifetime and quantum yield as reported in many cases. It was also reported that dyes adsorbed on cellulose are protected from quenching by molecular oxygen, as the mobility of this species is highly reduced in this medium, provided cellulose is well dried (20). In this way, interference from oxygen is easily avoided.…”
Section: Introductionmentioning
confidence: 99%
“…10 −3 mbar) at 60 °C for at least 24 h before sample preparation. The samples were prepared using the solvent evaporation method [30,31,32,33,34,35,36,40]. This method consists of the addition of a solution containing the indocarbocyanine in dried ethanol to the previously dried microcrystalline cellulose, followed by slow solvent evaporation from the slurry under stirring in a fume cupboard.…”
Section: Methodsmentioning
confidence: 99%
“…1 cm quartz cells were used for measurement of powdered samples. The remission function, F(R), of a probe adsorbed or included onto a solid powdered adsorbent and calculated with the use of the Kubelka-Munk equation for optically thick samples (F(R) = (1−R) 2 /2R ), after correction for the blank, is proportional to the host concentration [30,31,32,33,34,35,36,40]. Solution measurements were made using the same apparatus in the normal transmission mode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations